Long-term use of renin-angiotensin-system inhibitors after acute myocardial infarction is not associated with survival benefits: Analysis of data from the Korean acute myocardial infarction registry-national institutes of health registry - Park, Chan Soon; Yang, Han-Mo; Kang, Jeehoon; Han, Jung-Kyu; Park, Kyung Woo; Kang, Hyun-Jae; Koo, Bon-Kwon; Seung, Ki-Bae; Cha, Kwang Soo; Seong, In-Whan; Rha, Seung-Woon; Jeong, Myung Ho; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Renin-angiotensin-system inhibitors (RASi) have shown survival benefits after acute myocardial infarction (MI), but the role of routine long-term use of RASi remains unclear. Thereby, we explored the therapeutic effects of RASi medication at 1-year follow-up from acute MI. Methods Using the nationwide Korea Acute Myocardial Infarction Registry-National Institutes of Health (KAMIR-NIH) registry, we included and analyzed 10,822 subjects. Patients were stratified into those taking RASi at 1-year follow-up (n = 7,696) and those not taking RASi at 1-year follow-up (n = 3,126). Patients were followed up for 2-years from the 1-year follow-up; 2-year all-cause mortality and cardiac mortality were analyzed as primary and secondary outcomes, respectively. Results The use of RASi at 1-year follow-up was not associated with decreased all-cause mortality (log-rank P = 0.195) or cardiac mortality (log-rank P = 0.337). In multivariate analyses, RASi medication at 1-year follow-up did not reduce all-cause mortality (P = 0.758) or cardiac mortality (P = 0.923), while RASi medication at discharge substantially reduced 1-year all-cause and cardiac mortality. Treatment with either an angiotensin-converting enzyme inhibitor or angiotensin II receptor blocker at 1-year follow-up did not show survival benefits from 1-year follow-up, respectively. The use of RASi at 1-year follow-up did not show a prognostic interaction between previous history of chronic kidney disease, post-MI acute heart failure, concomitant use of beta-blockers at 1-year follow-up, or 1-year LVEF. Conclusion Acute MI patients taking RASi at 1-year follow-up were not associated with improved 2-year all-cause mortality or cardiac mortality from the 1-year follow-up. This study provides valuable information regarding tailored medication strategy after acute MI. Clinical trial registration [www.ClinicalTrials.gov], identifier [KCT0000863].